2021
DOI: 10.1029/2020je006539
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Exposed Dusty Water Ice within Martian Gullies

Abstract: Background 1.1. H 2 O Ice on Mars The presence of H 2 O ice and liquid water is key to the evolution of Martian geology, with implications for the potential for past or extant life, and the future of robotic and human exploration on Mars. H 2 O ice reservoirs hold key records of Mars' climate history, and understanding the state and evolution of subsurface ice can provide insight on past and present-day processes on Mars. The obliquity of Mars is thought to have oscillated over recent timescales (10 5-10 6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 151 publications
(307 reference statements)
0
13
0
Order By: Relevance
“…Many gullies are incised into mantling materials (e.g., Christensen, 2003), which in many cases likely have a high H 2 O ice content because the total apron volumes are smaller than the eroded alcoves (Conway & Balme, 2014; Gulick et al., 2019). Khuller and Christensen (2021) documented exposure of bright material interpreted as water ice by slumping in several alcoves.…”
Section: Mass Wasting and Slope Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many gullies are incised into mantling materials (e.g., Christensen, 2003), which in many cases likely have a high H 2 O ice content because the total apron volumes are smaller than the eroded alcoves (Conway & Balme, 2014; Gulick et al., 2019). Khuller and Christensen (2021) documented exposure of bright material interpreted as water ice by slumping in several alcoves.…”
Section: Mass Wasting and Slope Processesmentioning
confidence: 99%
“…In aggregate, it appears that the morphology of gullies is currently being shaped by modern CO 2 frost processes, although a few studies still explore whether brines may be involved in the present‐day activity of linear dune gullies (e.g., Jouannic et al., 2019) and Khuller and Christensen (2021) suggested that melting in alcoves could occur in association with bright exposures. Dune gullies are so active that they must entirely form on timescales much less than obliquity cycles, and indeed a few new or completely redeveloped gullies are observed to form on sand dunes within a few Mars years (Dundas et al., 2012; Dundas, McEwen, et al., 2019).…”
Section: Mass Wasting and Slope Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence, stability, and physical nature of H 2 O ice on Mars has major implications for understanding martian history, evolution, and future robotic and manned exploration. However, the pervasive presence of dust on Mars causes the ice to contain typically <∼1% dust, especially when exposed at the mid‐latitudes (Dundas et al., 2018; Khuller & Christensen, 2021). The ice is thought to have been deposited as snow during periods of high obliquity that occurred numerous times over the last few million years (Christensen, 2003; Jakosky & Carr, 1985; Madeleine et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have indicated that dusty H 2 O ice is currently being exposed at martian mid‐latitudes (e.g., Byrne et al., 2009; Dundas et al., 2018; Khuller & Christensen, 2021). The precise nature (grain size and dust content) of this exposed ice is currently uncertain, and estimates of the time scale of martian snow metamorphism range from decades/centuries (Clow, 1987; Kieffer, 1990) to millions of years (Bramson et al., 2017).…”
Section: Introductionmentioning
confidence: 99%